The nature of chemical neurotransmission - Leonard, Brian (Henry Stewart Talks, 2007)
Chemical neurotransmission, What is a neurotransmitter?, Neurotransmission: mechanism of action, Mechanisms governing neurotransmitter release, Different types of receptor, Switching off neurotransmitters, Synthesis and metabolism of acetylcholine, Gases as neurotransmitters, Presynaptic modulation of neurotransmission, Is the brain "hard-wired" or "plastic"?